NOTES ON MALAYSIAN MALVACEAE-I * - WAALKES, J. VAN BORSSUM (Research Center for Biology, 1956)
Twelve new species of Hibiscus sect. Azanza DC. from the Malaysian region are described and illustrated. The genus Wilhelminia Hochr. is reduced to a synonym of this section, which requires the new combination Hisbiscus sciadiolepidns (Hochr.) Borss. for W. sciadiolepida Hochr. the only species of the genus.